Penilaian Tingkat Kesehatan Keuangan pada PT. Jasa Marga Persero Tbk Periode 2018–2022 - Dhini Ramadhanty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Assessing the level of financial health of a company is an important thing that can help evaluate the company's current and past financial position and operating results. This also does not fail to happen to State-Owned Enterprises (BUMN). To measure financial performance or health, the Ministry of BUMN has regulated it and made it an assessment standard for BUMN, which is stated in the Decree of the Minister of BUMN No. KEP-100/MBU/2002. This research aims to analyze the financial statements for the 2018–2022 period of PT. Jasa Marga Persero Tbk based on the Ministerial Decree. This research uses quantitative data measured on a numerical scale. This research uses quantitative descriptive analysis, which explains the research results in the form of financial report data related to company performance. The data is in the form of accounting information which will then be analyzed using the necessary financial ratios and can show information regarding liquidity, solvency, activity and profitability. The research results show that the assessment of the health level of PT. Jasa Marga (Persero) Tbk. 2018–2022 based on the Decree of the Minister of BUMN No. KEP-100/MBU/2002, if seen from the profitability and the liquidity ratio is considered to be getting better, while the activity and solvency ratio is considered to be less good. Apart from that, the research results also showed that the level of financial health was “not healthy,” but in 2022 the health level of PT. Jasa Marga (Persero) Tbk improved to “healthy.”